2019
DOI: 10.1523/jneurosci.0774-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Cytoplasmic DNA Due to ATM Deficiency Activates the Microglial Viral Response System with Neurotoxic Consequences

Abstract: ATM (ataxia-telangiectasia mutated) is a PI3K-like kinase best known for its role in the DNA damage response (DDR), especially after double-strand breaks. Mutations in the ATM gene result in a condition known as ataxia-telangiectasia (A-T) that is characterized by cancer predisposition, radiosensitivity, neurodegeneration, sterility, and acquired immune deficiency. We show here that the innate immune system is not spared in AT. ATM-deficient microglia adopt an active phenotype that includes the overproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 86 publications
(91 reference statements)
11
115
2
Order By: Relevance
“…Additionally, caspase-1 can cleave gasdermin D to initiate pyroptotic cell death, characterized by the formation of pores in the plasma membrane and the release of cellular contents into the extracellular environment (Kayagaki et al, 2015;Shi et al, 2015). The AIM2 inflammasome has been shown to form following infection with either DNA or RNA viruses in peripheral myeloid and lymphoid immune celltypes, such as bone marrow derived dendritic cells (BMDCs), bone marrow derived macrophages (BMDM), monocytes, and fibroblasts (Rathinam et al, 2010;Ekchariyawat et al, 2015;Schattgen et al, 2016;Huang et al, 2017;Zhang et al, 2017), and the role of this and other inflammasomes during viral infection is discussed extensively elsewhere (Chen and Ichinohe, 2015;Lupfer et al, 2015;Man et al, 2016;Shrivastava et al, 2016;Lugrin and Martinon, 2018;Zhu et al, 2019).…”
Section: Aim2mentioning
confidence: 99%
“…Additionally, caspase-1 can cleave gasdermin D to initiate pyroptotic cell death, characterized by the formation of pores in the plasma membrane and the release of cellular contents into the extracellular environment (Kayagaki et al, 2015;Shi et al, 2015). The AIM2 inflammasome has been shown to form following infection with either DNA or RNA viruses in peripheral myeloid and lymphoid immune celltypes, such as bone marrow derived dendritic cells (BMDCs), bone marrow derived macrophages (BMDM), monocytes, and fibroblasts (Rathinam et al, 2010;Ekchariyawat et al, 2015;Schattgen et al, 2016;Huang et al, 2017;Zhang et al, 2017), and the role of this and other inflammasomes during viral infection is discussed extensively elsewhere (Chen and Ichinohe, 2015;Lupfer et al, 2015;Man et al, 2016;Shrivastava et al, 2016;Lugrin and Martinon, 2018;Zhu et al, 2019).…”
Section: Aim2mentioning
confidence: 99%
“…In fact, a series of elegant studies provided evidence for replication stress-induced inflammation as a driver of neuronal degeneration in models of ataxia telangiectasia. Studies about the immune response in At −/− -mice revealed that the accumulation of cytoplasmic DNA in microglial cells triggered the release of neurotoxic cytokines, leading to chronic neuroinflammation and neurodegeneration [81,82]. Understanding the contributions of RSR to nervous system development, degeneration, and regeneration is of fundamental biomedical importance.…”
Section: Overview Of Dna Replication Stress: How Cells Prevent and Rementioning
confidence: 99%
“…A direct link of defective DDR, cGAS-STING pathway, inflammatory cytokines, and neurodegeneration was recently established. In Atm −/− mice: Atm-deficient microglia accumulate cytoplasmic DNA and trigger a STING-mediated proinflammatory response that secretes neurotoxic interleukins [81] (Figure 5). Consistent findings were also reported in a rat model of A-T [348].…”
Section: Non-cell-autonomous Rsr In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this concept to an example such as stroke, cytotoxic microglia is observed in the striatum, whereas subventricular zone microglia promote neurogenesis [59]. Furthermore, mouse models for amyotrophic lateral sclerosis exhibit neuroprotective microglia at disease onset, which is gradually transformed into cells with a more neurotoxic phenotype at the end of the disease [94]. Therefore, therapeutic intervention at the right place and time is vital to achieving success.…”
Section: Communication Between Microglia and Mscsmentioning
confidence: 99%